The mechanical origins of arm-swinging. Issue 130 (May 2019) - Granatosky, Michael C.; Schmitt, Daniel
Abstract: Arm-swinging is a locomotor mode observed only in primates, in which the hindlimbs no longer have a weight bearing function and the forelimbs must propel the body forward and support the entirety of the animal's mass. It has been suggested that the evolution of arm-swinging was preceded by a shift to inverted quadrupedal walking for purposes of feeding and balance, yet little is known about the mechanics of limb use during inverted quadrupedal walking. In this study, we test whether the mechanics of inverted quadrupedal walking make sense as precursors to arm-swinging and whether there are fundamental differences in inverted quadrupedal walking in primates compared to non-primate mammals that would explain the evolution of arm-swinging in primates only. Based on kinetic limb-loading data collected during inverted quadrupedal walking in primates (seven species) and non-primate mammals (three species), we observe that in primates the forelimb serves as the primary propulsive and weight bearing limb. Additionally, heavier individuals tend to support a greater distribution of body weight on their forelimbs than lighter ones. These kinetic patterns are not observed in non-primate mammals. Based on these findings, we propose that the ability to adopt arm-swinging is fairly simple for relatively large-bodied primates and merely requires the animal to release its grasping foot from the substrate. This study fills an important gap concerning the origins of arm-swinging and illuminates previously unknown patterns of primate locomotor evolution.